Improving Students’ Reading Comprehension of Narrative Texts through Students-team Achievement Division (STAD) Cooperative Learning: A Classroom Action Research at Grade IX of a Junior High School in Banten - Suarman, Asep (ENGLISH JOURNAL, 2016)
This paper presents the implementation of STAD cooperative learning (STAD CL) in teaching reading comprehension in one of Junior High Schools in Banten. It seeks to see whether STAD CL can enhance students’ comprehension in general and comprehension levels (literal, inferential and evaluative) in particular. It also reveals how students response to STAD CL. It employed classroom action research with two cycles of actions, involving 31 students. To collect data, observation, tests and questionnaire were done. The data indicate that STAD CL enhanced students’ comprehension in general. It also improved literal and evaluative levels. However, it did not enhance the inferential level of comprehension. In addition, STAD CL the data from questionnaire shows the students responded positively to STAD CL impact on their all comprehension levels. However, they are more aware of the impact on their literal comprehension level than that to inferential and evaluative levels. The suggestions are included.